Endoscopic Retrograde Cholangiopancreatography Findings Differs From Ultrasound Results: A Study On Choledocholitihisis Patients In A Tertiary Care Hospital Of Bangladesh - Bhiuyan, Tareq Mahmud; Sanyal, Mousumi; S, Sabrina Yesmin (Bangladesh Journal of Medicine, 2019)
Background: Endoscopic retrograde cholangio-pancreatography (ERCP) is a universally established modality in evaluation and treatment of pancreatico-biliary disorders. Choledocholothiasis is one of its common indications. In the context of Bangladesh, clinical studies on ERCP, specially, assessment of the role of pre-procedural Ultrasound as a screening tool, is relatively rare. In this work, we have analyzed the ERCP outcome of 95 patients and compared their pre-procedural ultrasound results afterwards. Methods: This cross-sectional observational study was conducted in the BIRDEM General Hospital during June 2013 to January2015 on 95 ERCP patients. Among 95 patients, maximum (27.7%) were diagnosed as Choledocholithiasis. The important diagnosis among the rest were, Chronic Calcific Pancreatitis (13.8%), Ca head of Pancreas (12.7%), Cholangiocarcinoma (11.7%), and peri- ampullary carcinoma (11.7%). Ultrasound could not detect common bile duct stone in 42% of choledocholithiasis patients. It detected dilated common bile duct in 30% patients and 15% patients had normal ultrasound report while they underwent ERCP due to high clinical suspicion and found to have duct stone afterwards. Conclusion: The role of ultrasound as a screening test for choledocholithiasis should be progressively assessed by comparing it with MRCP and ERCP results. This study will encourage further research to find correlation between the ERCP and Imaging (both ultrasound and MRCP) in choledocholithiasis patients Bangladesh J Medicine Jan 2019; 30(1) : 5-8